2016
DOI: 10.1007/s11064-016-1905-1
|View full text |Cite
|
Sign up to set email alerts
|

Crocin Upregulates CX3CR1 Expression by Suppressing NF-κB/YY1 Signaling and Inhibiting Lipopolysaccharide-Induced Microglial Activation

Abstract: Glaucoma is a group of neurodegenerative diseases characterized by the progressive loss of retinal ganglion cells (RGCs) and optic nerve fibers. Microglial activation has been shown to be deleterious to RGCs and may participate in the progression of glaucoma. Crocin, one of the major active ingredients in saffron, has been found to inhibit microglial activation. However, the mechanism remains unclear. The aim of this study was to investigate whether crocin can inhibit lipopolysaccharide (LPS)-induced microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…Focusing our study on specific keratinocytes cytokines as well as NF-jB signallingthe latter being highly involved in accelerating the ageing process [6,62,63]we first found that crocin was endowed with anti-inflammatory properties. Consistent with crocin inhibitory effects on LPS-induced inflammation in microglial cells and NF-jB signalling [64], crocin was found to inhibit the expression of IL8, PGE2, IL6, TNFa, IL1a and LTB4 pro-inflammatory mediators by PMA/A23187-treated NHEK. In a second set of experiments, the expression of a number of NF-kBdependent genes [65] was found modulated in NHEKS grown in the presence of 1 mM crocin, with a strong inhibition of inflammatory response genes and a stimulation of stress defence-related genes.…”
Section: Discussionsupporting
confidence: 60%
“…Focusing our study on specific keratinocytes cytokines as well as NF-jB signallingthe latter being highly involved in accelerating the ageing process [6,62,63]we first found that crocin was endowed with anti-inflammatory properties. Consistent with crocin inhibitory effects on LPS-induced inflammation in microglial cells and NF-jB signalling [64], crocin was found to inhibit the expression of IL8, PGE2, IL6, TNFa, IL1a and LTB4 pro-inflammatory mediators by PMA/A23187-treated NHEK. In a second set of experiments, the expression of a number of NF-kBdependent genes [65] was found modulated in NHEKS grown in the presence of 1 mM crocin, with a strong inhibition of inflammatory response genes and a stimulation of stress defence-related genes.…”
Section: Discussionsupporting
confidence: 60%
“…Further indication that modulation of microglial activation by CX3CL1/CX3CR1 in MSA comes from our demonstration of increased expression of CX3CR1 in MSA. In the context of data from a model of glaucoma in which an anti-inflammatory agent, crocin, successfully reduced microglial activation via CX3CR1 upregulation, this might indicate an anti-inflammatory effect in MSA ( 49 ). These results support our findings that there is no significant alteration in Iba-1 protein in the frontal lobe and inflammatory cytokines were unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Microglial activation in the early stages has been shown to be an indicator of neurodegeneration severity in glaucoma. A recently published study has investigated the role of crocin in the inhibition of lipopolysaccharide-induced microglial activation, and determined that crocin effectively suppresses microglial activation and NF-κB/YY1 signalling, inducing an upregulation of CX3CR1 expression [33] .…”
Section: Discussionmentioning
confidence: 99%